Attacking performance profile of football teams in different national leagues according to UEFA rankings for club competitions - Leontijevic, B.; Jankovic, A.; Tomic, L. (Facta Universitatis: Series Physical Education and Sport, 2018)
The aim of this study was to compare the attacking performance profiles of the football teams playing in the national leagues of different rankings, defined on the basis of the Union of European Football Associations (UEFA) coefficient regarding club competitions. Applying the method of random sampling, one national league belonging to the first group - 4 participants in the Champions League and 3 teams participating in the Europa League (CL4+EL3; Germany), one belonging to the second group - CL3+EL3 (France), one belonging to the third group (CL2+EL3; Austria) and one from the fourth group - CL1+EL3 (Serbia) were selected. The analysis included all championship matches within the mentioned national competitions during the 2016/2017 season, which was a total of 1162 matches. The variables related to ball possession, passing game structure and efficacy and goal scoring attacks were monitored (19 variables in total). The results of this study have shown that there are significant differences in the organization of attacking games by the teams competing in the leagues of different rankings. It can be concluded that the players of the teams from the German and French leagues possess higher quality in technical and tactical sense, and are trained to play extremely fast, with a high degree of success in ball control.